CHILDFREE DALAM PERSPEKTIF HUKUM KELUARGA ISLAM DAN HUKUM YURIDIS - Azila Ramadhani; Nabila Qatrunada; Siti Syahrina; Muhamad Parhan (SAMAWA, 2026)
The childfree phenomenon has become an important issue in the study of Islamic family law in Indonesia because it creates tension between the interpretation of maqashid al-shariah, particularly the principle of hifz al-nasl, and the individual's freedom to choose not to have children. This study aims to analyze the position of Islamic family law on childfree, identify the legal and social challenges faced by childfree families, and formulate a modern Islamic legal approach that is responsive to this phenomenon. The research method used is descriptive qualitative with a normative approach through literature study and content analysis. The results show that modern Islamic law provides space for childfree individuals on the condition that there are sharia reasons such as health conditions, family interests, and socio-economic factors that affect quality of life. In addition, laws and human rights support reproductive freedom as long as it is in accordance with religious norms and does not harm others. In conclusion, contemporary Islamic family law can adapt to modern social realities without neglecting religious principles and social responsibilities. This adaptation opens up space for respect for individual freedom in choosing a lifestyle, including childfree, as long as the decision is made with careful consideration and takes into account the broader interests of the community. Keywords: Childfree, Islamic family law, reproductive rights, maqashid al-shariah, social stigma